Does abnormal interhemispheric inhibition play a role in mirror dystonia?. Issue 6 (18th December 2013) - Sattler, Virginie; Dickler, Maya; Michaud, Martin; Meunier, Sabine; Simonetta‐Moreau, Marion
Abstract The presence of mirror dystonia (dystonic movement induced by a specific task performed by the unaffected hand) in the dominant hand of writer's cramp patients when the nondominant hand is moved suggests an abnormal interaction between the 2 hemispheres. In this study we compare the level of interhemispheric inhibition (IHI) in 2 groups of patients with writer's cramp, one with the presence of a mirror dystonia and the other without as well as a control group. The level of bidirectional IHI was measured in wrist muscles with dual‐site transcranial magnetic stimulation with a 10‐millisecond (short IHI) and a 40‐millisecond (long IHI) interstimulus interval during rest and while holding a pen in 9 patients with mirror dystonia 7 without mirror dystonia, and 13 controls. The group of patients without mirror dystonia did not differ from the controls in their IHI level. In contrast, IHI was significantly decreased in the group of patients with mirror dystonia in comparison with the group without mirror dystonia and the controls in both wrist muscles of both the dystonic and unaffected hand whatever the resting or active condition (P = 0.001). The decrease of IHI level in the group of patients with mirror dystonia was negatively correlated with the severity and the duration of the disease: the weaker the level of IHI, the more severe was the disease and the longer its duration. Interhemispheric inhibition disturbances are most likely involved in the occurrence of mirror dystonia. This bilateral deficient inhibition further suggests the involvement of the unaffected hemisphere in the pathophysiology of unilateral dystonia. © 2013 International Parkinson and Movement Disorder Society